2010
DOI: 10.1002/macp.200900472
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemistry of Schiff Base Cobalt(III) Complexes and Their Catalytic Activity for Copolymerization of Epoxide and Carbon Dioxide

Abstract: A series of cobalt complexes with N,N,O,O‐tetradentate Schiff base ligands were prepared. All the complexes were characterized by spectroscopy and electrochemical methods. An X‐ray crystal structure analysis revealed that L1‐CoIII‐dnp was monomeric with a six‐coordinated central cobalt(III) atom in the solid state. The complexes were employed as catalysts for the alternating copolymerization of CO2 and racemic propylene oxide. End group analysis of the resulting polymer provided strong evidence for a monomer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Numerous attempts to isolate complex 1 in some solvents proved to be unsuccessful. Compared with the structures of N,N'-bis(3,5-di-tertbutylsalicylidene)-1,2-cyclohexanediamine Co III 2,4-dinitrophenoxy (complex 2) and 2,2-dimethyl-1,3-propylene bis(3,5-di-tert-butylsalicylideneimino) Co III 2,4-dinitrophenolate, 26,27 complex 1 should be a stable six-coordinated central Co octahedron (Figure 1). Simple Salen Co III X complexes alone have proven to be inactive under low CO 2 pressure or at elevated temperature, where they are reduced to Co II derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous attempts to isolate complex 1 in some solvents proved to be unsuccessful. Compared with the structures of N,N'-bis(3,5-di-tertbutylsalicylidene)-1,2-cyclohexanediamine Co III 2,4-dinitrophenoxy (complex 2) and 2,2-dimethyl-1,3-propylene bis(3,5-di-tert-butylsalicylideneimino) Co III 2,4-dinitrophenolate, 26,27 complex 1 should be a stable six-coordinated central Co octahedron (Figure 1). Simple Salen Co III X complexes alone have proven to be inactive under low CO 2 pressure or at elevated temperature, where they are reduced to Co II derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Methylene chloride, hexane and chloroform were distilled from CaH 2 under argon. N,N¢-[2,2¢-bis(nitrilomethylidyne)]bis [a-methyl-4-(morpholin-1-ylmethyl)-6-tert-butyl phenolato]-1,2-cyclohexanediamine 24,25 and N,N¢-[2,2¢-bis(nitrilomethylidyne)]bis[a-methyl-4-(morpholin-1-ylmethyl)-6-tert-butyl phenolato]-1,2-cyclohexanediamino [26][27][28][29] Co II were prepared according to methods reported in the literature.…”
Section: Experimental Procedures Materialsmentioning
confidence: 99%
“…The intramolecular electron transfer and proton transfer reactions of Schiff bases containing nitrogen, sulphur and/or oxygen have been extensively investigated over few decades owing to their rich photochemical and photophysical properties which enables them to find wide range of important applications [17][18][19][20]. Heterocyclic Schiff base like benzothiazole, benzoxazoles and benzimidazole which are also medicinally important compounds as they comprise bioactive scaffold of many drugs [8].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 2, the structure is indeed a six-coordinate octahedral as the structure of the salen Co III (2,4-dinitrophenoxy) [35, 36]. X-ray diffraction data showed that the crystal was analogous monomeric structures.…”
Section: Resultsmentioning
confidence: 77%
“…Coates and coworkers [34] reported that a five-coordinated cobalt complex is pseudo square-pyramidal with Co located slightly above the plane of the salen ligand in the direction of the axial ligand. Recently, we reported the X-ray crystal structure of the salen Co III (2,4-dinitrophenoxy) is six coordinated [35, 36]. As far as we are aware, the crystal structure of the cobalt Schiff base complexes with axial acetate ligand has not been reported.…”
Section: Introductionmentioning
confidence: 99%